PENGARUH PENAMBAHAN SERBUK GAHARU (Aquilaria malaccensis) TERHADAP KARAKTERISTIK BRIKET ARANG AROMATERAPI DARI LIMBAH ARANG SERBUK KAYU CAMPURAN - Eky Saputra; Violet Violet; Noor Mirad Sari (Jurnal Sylva Scienteae, 2020)
This studygaims to analyze the characteristics of aromatherapy charcoal briquettes from mixed wood charcoal powder waste and agarwood wood carried out organoleptic tests in the form of the old ability to burn briquettes to ash  when aromatherapy charcoal spreads in a room. The results of the study showed that of the highest charcoal briquette density average value was (0.90 gr/cm3) and the lowest (0.82 gr/cm3), highest moisture content value of (9.33%) and the lowest of (8.46%). Value of flying substances levels (47.9%)  and the lowest is (40.66%). Value of the highest ash content characteristics of (40.37%) and the lowest (33.28%). Testing the highest average value of bonded carbon characteristics is 28.82% and the lowest is (9.305%). Value of the highest heating characteristics (4174,696 cal/gr) and the lowest (3784,976 cal/gr). From all the results of the testing of the characteristics of the aromatherapy charcoal briquettes from the mixture of wood charcoal powder and agarwood powder waste on average do not meet ASTM testing standards. The organoleptic test of mold without holes that most quickly consumes aromatherapy at a concentration of 6 grams with 5 minutes and the longest smell of aromatherapy is 12, 18, and 24 grams with 7 minutes with an average of 46 minutes. And organoleptic test with the fastest hollow molds smelled at concentrations of 12 grams, 18 grams, 24 grams at 15 seconds, and on average each concentration had a scent that runs out at 7 minutes with an average of 55 minutes long liters of briquettes.Keywords : Characteristics of Charcoal Briquettes; Organoleptic Test; Mixed Wood Charcoal Waste and Agarwood